Webinar insights: Pathways to more jobs and better incomes in agrifood systems - Nguyen, Vi (International Food Policy Research Institute, 2023)
Building inclusive and sustainable agrifood systems can play a key role in achieving sustainable development goals. Agrifood systems account for more than 70% of employment in low-income countries and employs more than 1 billion people worldwide. Yet achieving equitable and inclusive livelihoods and employment is at risk.